Understanding academic coaching at community colleges: a multi-case study - Joiner, Stephanie Anne (Kansas State University, 2024)
Community colleges play an important role in providing access to higher education to underserved student populations who often arrive on campus underprepared for the academic rigor of a college classroom. To support these students, many community colleges have implemented academic coaching programs. Built from professional coaching practices, early studies on academic coaching indicate that it can have a positive impact on student retention and completion rates; however, much of that research has largely focused on the quantitative effects of the practice at four-year institutions, and research conducted on academic coaching at community colleges has indicated difficulty in identifying consistent use of a coaching framework and evaluating it as a practice. This qualitative multi-case study addresses the gap in the literature by investigating shared practices and experiences of three community college academic coaching programs. With the resulting holistic analysis of academic coaching in community colleges using Ives’ (2008) coaching dichotomies, this study provides an updated definition of academic coaching in the community college context and implications for practice and creating an opportunity for future studies to evaluate effectiveness of coaching programs.
Keywords: Academic coaching; Community college; Multi-case study; Student support